Illegal settlement in the Babile Elephant Sanctuary is threatening the resident elephant population. Issue 3 (30th May 2022) - Neil, Emily; Greengrass, Elizabeth
Abstract: The Babile Elephant Sanctuary in Ethiopia was established in 1970 specifically to protect its elephants Loxodonta africana. They were once part of a larger population that ranged in eastern Ethiopia and northern Somalia but that was largely extirpated during the 20th century. Since its establishment, the Sanctuary has experienced severe anthropogenic pressure, inadequate government support, and civil conflict. Mapping was undertaken to analyse the rate of human immigration into the Sanctuary in 2006, 2014 and 2017, as part of an assessment of the Sanctuary's effectiveness in protecting its resident elephant population and in mitigating anthropogenic pressures. From 2006 to 2017 the number of illegal houses in the Sanctuary increased from 18, 000 to > 50, 000, of which > 32, 000 were in the area in which elephants range. This settlement, coupled with high demand for natural resources, has resulted in significant habitat destruction and could also have exacerbated human–elephant conflict. Elephant conservation and monitoring by the Born Free Foundation were challenging because of ethnic conflict; rural and political stability is required if efforts to protect wildlife are to be successful. Unless these issues are resolved and the integrity of the Sanctuary is restored, this elephant population will be extirpated in the near future.